A Note on the Brand Names for "Bath Salts". (March 2014) - Nuessel, Frank
<x content-type="archive" xml:space="preserve">Abstract</x> This essay discusses a relatively recent phenomenon, namely, the sale and use of a synthetic chemical product known generically as "bath salts." It then defines this term. Next, it discusses selectively the scientific literature on this product. Finally, it interprets the significance the brand names used to refer to the product and their referents within an onomastic and semiotic framework.